Engaging me softly: Comparing social drivers for continuative citizens’ participation in a long-term citizen science initiative on protected species monitoring - Silvia Gisondi; Paolo Giardullo; Alice Lenzi; Emanuele Di Buccio; Pio Federico Roversi; Alessandro Campanaro (PLoS ONE, 2025)
The engagement of volunteers in Citizen Science (CS) projects is a relevant issue that needs to be addressed to ensure long-term sustainability, scientific relevance, and public participation. Given this, the present paper analyses the social drivers of volunteers’ involvement in a long-term CS initiative to monitor protected species and habitats all over Italian national territory. This initiative was initially born as the LIFE11 NAT/IT/000252 MIPP (Monitoring of Insects with Public Participation), then changed name to “InNat” benefitting from Italian national fundings, and it finally ended in 2024. Overall, it counts more than 1600 participants to whom a dedicated survey was submitted in 2022 to compare and analyse different factors potentially driving participation (potential enablers) and fostering engagement within the project. Based on the survey results (22.3% response rate of 1632 invitations sent), different drivers for participation are modelled (socio-demographic features, interest in scientific topics, environmental attitudes) considering the following main factors: (i) the level of commitment to the initiative, (ii) the seniority of the citizen scientist involved, (iii) the attitudes towards nature conservation and species monitoring, (iv) the value assigned to CS activities. In this context, socio-demographic variables have been compared to attitudes and practices connected to open-air monitoring activities (e.g., recording protected species and habitats by taking pictures in nature). The proposed analyses tackle a variety of cultural and social components as well as their relationship, highlighting some of the features (e.g., active interest in CS activities reverberating in both commitments to engage other volunteers and active search for CS initiatives) that characterize constant participation. We classified volunteers into two categories (i.e., Consistent Volunteers and Non-Consistent Volunteers), comparing these two categories along potential enablers of engagement. Results show homogeneity among volunteers for several parameters (e.g., similar education level, age, occupational status) but also differences in personal motivation and active interest in citizen science initiatives.